Ø±Ø¹Ø§ÙŠØ© Ø§Ù„Ø¨ÙŠØ¦Ø© ÙÙŠ Ø§Ù„ØªØµÙˆÙ Ø§Ù„Ø¥Ø³Ù„Ø§Ù…ÙŠ - Munji, Ahmad (Fakultas Ushuluddin dan Humaniora - UIN Walisongo Semarang, 2016)
As a universal religion, Islam regulates all aspects of life. As one of aspects in Islam, tasawwuf/Sufism invites people to be guardians for environmental preservation since nature is part of God’s creatures. To some extent, the teachings of Sufism are mainly about ethic (adab). This ethic can be either vertical to God or horizontal to all God’s creatures including nature and environment. Ibn Arabi in this regard is an influential character in Sufism which his thoughts gave a lot of influence on the development of the world of Sufism in General. Among his thoughts is about the unity of God with the universe. The question is, how Ibn Arabi’s thought could give an impact in the context of the preservation of the environment. This research finds amd formulates some aspect of Sufism that can contribute to encourage people in dealing with environmental preservation. It is based on attitude or akhlak theologically.